THE IMPORTANCE OF ENGLISH IN TOURISM AND HOSPITALITY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article discusses the importance of English in tourism and hospitality industries. English has become the global language of communication and plays a significant role in international tourism. The research explains how English helps employees communicate effectively with tourists, improve customer service, and develop professional careers. The article also analyzes the role of English in hotels, restaurants, airports, and travel agencies. The study is written in IMRAD format and is based on qualitative analysis using educational and tourism-related sources. The results show that English proficiency increases service quality, customer satisfaction, and employment opportunities in tourism and hospitality sectors.
Keywords: English language, tourism, hospitality, communication, international service, career development.